The INFLUENCE OF BULOG'S ROLE ON COMMUNITY FOOD SECURITY THROUGH THE EFFECTIVENESS OF THE SPHP PROGRAM (FOOD SUPPLY AND PRICE STABILITY) AS A MEDIATING VARIABLE IN THE CITY OF JAMBI - Zorif, Muhammad Aqshal; Yacob, Syahmardi (Journal of Business Studies and Management Review, 2026)
This study analyzes the influence of the role of Perum BULOG on community food security in Jambi City, with the effectiveness of the Food Supply and Price Stabilization Program (SPHP) as a mediating variable. Food security is determined not only by food availability but also by people’s economic access to food at stable and affordable prices. In Jambi Province, limited local rice production and dependence on interregional supply make rice prices vulnerable to fluctuations, which can threaten household food security, especially among low-income groups. Therefore, BULOG plays a strategic role in procurement, storage, distribution, and price control of rice to maintain supply and price stability. This research applies a quantitative approach using proportional random sampling. Data were collected through questionnaires distributed to residents of Jambi City and analyzed using the Partial Least Squares (PLS) method with SmartPLS software. The study is based on Entitlement Theory and Program Effectiveness Theory, which explain how government intervention and program performance affect community access to food. The results show that the role of BULOG has a positive and significant effect on the effectiveness of the SPHP program and on community food security, while the effectiveness of the SPHP program significantly affects food security at the 10% significance level but does not mediate the influence of BULOG’s role. These findings indicate that food security in Jambi City is directly influenced by BULOG’s operational functions than by the indirect mechanism of SPHP effectiveness. Keywords: Role of BULOG, Food Security, SPHP Program Effectiveness, Price Stabilization, Jambi City.